The Importance of Using Applied Mathematics in Teaching Process (Journal of Pedagogical Inventions and Practices, 2022)
The article highlights the importance of training competitive personnel in higher education institutions based on the needs of economic sectors and industries on the example of mathematics. For this purpose, reiterated the importance of promotion of vocational training, development of the student's independent learning skills, as well as organization of development of student competence in the field.